Assessment of Upper and Lower Airway Dimensions in Skeletal Class I and Class II Subjects Having Different Growth Patterns - A Cross-Sectional Cephalometric Study - Hrushikesh S. Aphale; Sunilkumar L. Nagmode; Sejal P. Surana; Akshay S. Chaugule; Vivek J. Shinde; Dipak S. Sahane (Wolters Kluwer Medknow Publications, 2024)
Objectives: To compare the airway dimensions among subjects having skeletal class I and class II patterns considering their hypodivergent, normodivergent, and hyperdivergent growth patterns and to determine any variations between them. Methods and Materials: The study consisted of 156 pre-treatment lateral cephalograms of subjects aged above 18 years. The sagittal skeletal pattern was used to separate the sample into two groups. Each group was further subdivided into hypodivergent, normodivergent, and hyperdivergent growth patterns. The upper and lower airway dimensions were measured in all the subgroups. The intragroup comparison of class I and class II was performed with 1-way ANOVA and post-hoc test. Using the independent t-test, the upper and lower airways were compared between groups. Results: Comparison of subjects according to the growth pattern showed that vertical growth patterns have statically significantly reduced upper and lower airway dimensions as compared to the average and horizontal growth patterns in both skeletal class I and class II subjects. However, the subjects with skeletal class II hyperdivergent growth patterns have significantly reduced lower airway dimensions than those with skeletal class I having hyperdivergent growth patterns. Conclusion: Individuals with skeletal class I and class II patterns characterized by hyperdivergent growth exhibit reduced upper and lower pharyngeal airways. The sagittal skeletal type also plays a role in influencing the dimensions of the upper and lower airways.